Proceedings of the 3rd International Conference on Advances in Energy and Environmental Science 2015 2015
DOI: 10.2991/icaees-15.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intercropping Density of Galinsoga parviflora on Cadmium Accumulation of Soybean

Abstract: Abstract:The effects of intercropping different density (1, 2, 3, 4 and 5) of cadmium (Cd) hyperaccumulator Galinsoga parviflora on cadmium accumulation of soybean were investigated through pot experiment. The results showed that intercropping with 1 G. parviflora seedling increased biomass of soybean compared with monoculture, and decreased when intercropping with 2, 3, 4 and 5 G. parviflora seedlings. Intercropping with different density of G. parviflora decreased Cd content in soybean compared with monocult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
3
1
0
Order By: Relevance
“…[11][12][13] In this study, cherry intercropped with S. photeinocarpum and its post-grafting generations increased the biomass of cherry to some extent, while decreased the biomass of S. photeinocarpum and its post-grafting generations. These results are consistent with previous studies, 24,31,32 indicating that competition was mainly involved in the intercropping system of cherry and S. photeinocarpum or its post-grafting generations. In this study, the biomass of cherry seedlings was higher than S. photeinocarpum and its post-grafting generations.…”
Section: Discussionsupporting
confidence: 93%
“…[11][12][13] In this study, cherry intercropped with S. photeinocarpum and its post-grafting generations increased the biomass of cherry to some extent, while decreased the biomass of S. photeinocarpum and its post-grafting generations. These results are consistent with previous studies, 24,31,32 indicating that competition was mainly involved in the intercropping system of cherry and S. photeinocarpum or its post-grafting generations. In this study, the biomass of cherry seedlings was higher than S. photeinocarpum and its post-grafting generations.…”
Section: Discussionsupporting
confidence: 93%
“…Similar observations on the concentration and accumulation of Cd in silage maize shoots were obtained in the CIS systems ( Table 5 ). Generally, our results are in good agreement with the findings of Lin et al [ 41 ] and Ma et al [ 42 ], who also observed positive density-dependent uptake of Cd by Gallant soldier plants.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to the peat-amended treatments, the results of non-amended treatments showed that even though the plant density reached 4 plants per pot, the shoot biomass of individual Indian mustard plants did not change significantly in the MI and CIS systems ( Supplemental Figure S2 ). With or without peat amendment, our results obtained in the CIS systems are consistent with the findings of Lin et al [ 41 ] and Ma et al [ 42 ], who observed a similar phenomenon in their inter-cropping studies on the relationship between hyperaccumulator Gallant soldier ( Galinsoga parviflora ) density (2 and 4 plants pot −1 ) and individual shoot biomass. However, the authors also found that, when Gallant soldier plants were inter-cropped with radish ( Raphanus sativus ) or soybean ( Glycine max ), the shoot biomass of individual Gallant soldier plants increased with increasing plant density up to 3 plants per pot [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation